The effectiveness of the organization in the philosophy of the most prominent theoreticianAdministrative thought - العنزي, سعد; عدنان, يعرب; النوري, احمد نزار (Journal of Economics and Administrative Sciences, 2009)
This paper discuses the mindset contribution of the organization Science in organizational effectiveness (OE), and the most valuable thoughts they introduced in this subject, starting from the pre- classical era, through classical era to present time. This paper has identified the main contribution in OE. The concept of OE didn’t arise until what had been introduced by Chester Barnard, although Max Weber mentioned this concept in his bureaucratic theory, but he didn’t explain it as Barnard does. After that no clear focus was pointed to this subject until Peter Drucker did so, which considered as the main participant in OE after Barnard. After that many researchers be interested in OE and they start studying this subject like , Likert, McGregor, Scott and else. More attention had been given to OE in the eighties and nineties of the Past century which witnessed the introduction of many different integrated approaches specialized in studying the organizational effectiveness concept.